Effect of aging treatment on the microstructural evolution and mechanical properties of Co-free maraging steel manufactured by wire arc directed energy deposition - Zhanlin Ma; Yangling Ou; Junqiang Xu; Qianli Zhu; Runchang Liu; Xiaotian Zhang; Zhen Wang; Qi Zhou; Yong Peng; Kehong Wang (Journal of Materials Research and Technology)
In this study, a Co-free maraging steel was fabricated using the wire arc directed energy deposition technique and the effect of aging treatment on the microstructural evolution as well as the mechanical properties was investigated. The microstructure consisted of martensite and a small amount of austenite both before and after aging treatment. Due to the reverse transformation of austenite, the volume fraction of austenite in the aged samples increased. Additionally, aging treatment is able to enhance the texture characteristics of the martensite. During this process, the grain size remained largely unchanged, and the elements between the dendrites did not redistribute. Due to the precipitation of Ni3Ti nanoparticles after aging, the microhardness, yield strength, and ultimate tensile strength of the aged state increased by 30.1 %, 34.8 %, and 13.7 %, respectively, while the elongation after fracture remained essentially unchanged. The increase in yield strength is primarily attributed to the precipitation strengthening effect of the nanoscale precipitates.